A Visible and Near‐Infrared Light‐Fueled Omnidirectional Twist‐Bend Crawling Robot. (3rd February 2023) - Qian, Nina; Bisoyi, Hari Krishna; Wang, Meng; Huang, Shuai; Liu, Zhongcheng; Chen, Xu‐Man; Hu, Jun; Yang, Hong; Li, Quan
Abstract: In recent years, although light‐driven soft actuators have attracted intense scientific attention and achieved remarkable progress, the design and construction of an intelligent robotic system with maneuverability, self‐adaptability, untethered control, and greater freedom of action, in particular the omnidirectional motion capability on a plane, remains challenging. Herein,  four types of photo‐thermal fillers and an unprecedented twist‐bend actuation mode is introduced into a liquid crystal elastomer‐based soft robot. The obtained twist‐bend crawling robot not only exhibits in situ rotation, four‐way turning, and four‐way linear motion under light irradiation with four wavelength bands (520, 655, 808, and 980 nm), but also demonstrates the ability to avoid obstacles in complex geographical environments. This work may bring a new perspective for fabrication and development of soft robots that can adapt to dynamic and complex environmental conditions. Abstract : A light‐fuelled omnidirectional crawling soft robot is constructed by introducing twist‐bend motion mode. Four less‐interfered photo‐thermal fillers are employed to realize visible/IR wavelength‐selective controllability of the robot. Such twist‐bend crawling robot exhibits in situ rotation, four‐way turning, and four‐way straight moving, and even proves to have the ability to avoid obstacles in complex geographical environments.